Thermal Comfort Identification of Traditional Bugis House in Humid Tropical Climate - Sahabuddin Latif; Baharuddin Hamzah; Ramli Rahim; Rosady Mulyadi (Tesa Arsitektur, 2019)
This study aims to determine the thermal comfort conditions in the interior of traditional Bugis houses in South Sulawesi. This phase measured 18 (eighteen) houses by collecting data on 2 (two) main variables of room thermal comfort, namely air temperature and relative humidity. The recording time starts from 08.00 to 16.00 WITA. Observation made to collect room geometry data, building orientation, roof slope, and material used. Measuring instruments are placed in the living room throughout the room. The analysis carried out on the measurement data is then correlated with the observation. The results show that the average outside temperature above the thermal comfort standard is around 32.0 to 37.4℃ from morning to afternoon, the maximum temperature reaching 41.7℃ occurs around 13.00 to 14.00 WITA and the minimum temperature is 28.2℃ only occurs in the morning. Air humidity average is relatively fair in the thermal comfort zone between 42.8 to 69.8%. Material gives the most dominant influence on heat induction from the outside environment to the interior space. The orientation of the house found in North-South is hotter, the roof with a double slope is hotter, and the lower the ceiling is more hot.